Key Communicator Networks used in Dissemination of Agricultural Information: A Study in Koya Sub-tribe Setting - P.L.Manohari (Journal of Agricultural Extension Management, 2025)
Effective communication of scientific findings to the millions of farmers is a necessity and key to economic progress of the nation. This is more so in developing countries like ours, where the gap between intellectuals and the common man is very wide. The gap is much more wider in tribal farmers when compared to the non-tribal farmers. As the prosperity of a nation depends largely on the agricultural development, communication is apparently applicable to the development of agriculture because it is the fundamental step in bringing about a desirable change in any aspect of client system